THE USE OF MASK AND STRETCHING THE SHAF OF JUSTICE PRAYERS IN THE PANDEMIC PERIOD IN MUI FATWA NUMBER 31 OF 2020: QAWAID FIQHIYYAH PERSPECTIVE - Zainuddin Puteh; Dhiauddin Tanjung (Universitas Islam Negeri Ar-Raniry, 2022)
On June 4 2020, the Indonesian Ulema Council (MUI) issued fatwa Number 31 of 2020 concerning